Exploring Key Considerations for Artificial Intelligence Robots in Home Healthcare Using the Unified Theory of Acceptance and Use of Technology and the Fuzzy Analytical Hierarchy Process Method - Keng-Yu Lin; Kuei-Hu Chang; Yu-Wen Lin; Mei-Jin Wu (Systems)
Most countries face declining birth rates and an aging population, which makes the persistent healthcare labor shortage a pressing challenge. Introducing artificial intelligence (AI) robots into home healthcare could help address these issues. Exploring the primary considerations for integrating AI robots in home healthcare has become an urgent topic. However, previous studies have not systematically examined the factors influencing elderly individuals’ adoption of home healthcare AI robots, hindering an understanding of their acceptance and adoption. Furthermore, traditional methods overlook the relative importance of each consideration and cannot manage the ambiguity inherent in subjective human cognition, potentially leading to biased decision-making. To address these limitations, this study employs the unified theory of acceptance and use of technology (UTAUT) as a theoretical framework, integrating the modified Delphi method (MDM) and the fuzzy analytical hierarchy process (FAHP) to identify the key considerations. The research determined the order of importance of four evaluation criteria and fourteen evaluation sub-criteria, revealing that customization, accompany, and subjective norms are key factors that influence elderly individuals’ adoption of home healthcare AI robots.